Antioxidative Reactivity of L-Ascorbic Acid and D-Isoascorbic Acid Species towards Reduction of Hexachloroiridate (IV) - Han Zhang; Yanqing Xia; Peng Zhang; Liqian Hou; Ying Sun; Zhaozhan Lu; Yunfeng Tang; Hongwu Tian; Tiesheng Shi (Journal of Chemistry)
The pair [IrCl6]2–/[IrCl6]3– has been demonstrated to be a good redox probe in biological systems while L-ascorbic acid (AA) is one of the most important antioxidants. D-isoascorbic acid (IAA) is an epimer of AA and is widely used as an antioxidant in various foods, beverages, meat, and fisher products. Reductions of [IrCl6]2– by AA and IAA have been analyzed kinetically and mechanistically in this work. The reductions strictly follow overall second-order kinetics and the observed second-order rate constants were collected in the pH region of 0 ≤ pH ≤ 2.33 at 25.0°C. Spectrophotometric titration experiments revealed a well-defined 1 : 2 stoichiometry, namely Δ[AA] : Δ[Ir(IV)] or Δ[IAA] : Δ[Ir(IV)] = 1 : 2, indicating that L-dehydroascorbic acid (DHA) and D-dehydroisoascorbic acid (DHIA) were the oxidation products of AA and IAA, respectively. A reaction mechanism is suggested involving parallel reactions of [IrCl6]2– with three protolysis species of AA/IAA (fully protonated, monoanionic, and dianionic forms) as the rate-determining steps and formation of ascorbic/isoascorbic and ascorbate/isoascorbate radicals; in each of the steps, [IrCl6]2– acquires an electron via an outer-sphere electron transfer mode. Rate constants of the rate-determining steps have been derived or estimated. The fully protonated forms of AA and IAA display virtually identical reactivity whereas ascorbate and isoascorbate monoanions have a significant reactivity difference. The ascorbate and isoascorbate dianions are extremely reactive and their reactions with [IrCl6]2– proceed with the diffusion-controlled rate. The species versus pH and the species reactivity versus pH distribution diagrams were constructed endowing that the ascorbate/isoascorbate monoanionic form dominated the total reactivity at physiological pH. In addition, the value of pKa1 = 3.74 ± 0.05 for IAA at 25.0°C and 1.0 M ionic strength was determined in this work.